Risk factors for prediabetes in young adults: a study based on Korea National health and nutrition examination survey data - Sujung Lee; Dae-Soon Son; Jae-In Kim; Jungmin Lee (Scientific Reports)
Abstract Diabetes is a growing health concern among young adults; yet, most studies focus on older populations. This study aimed to examine the factors associated with prediabetes development in young adults. We carried out a cross-sectional study using data from the Korean National Health and Nutrition Examination Survey (KNHANES) for the period 2013–2021. Young adults were categorized into prediabetes (n = 2306) and normal glucose (n = 2306) groups. Propensity score matching was applied to control for age and sex, and multiple logistic regression was performed to identify significant predictors for prediabetes. The results showed that glycated hemoglobin had the highest adjusted Odds Ratio (OR = 2.27, p < 0.001), confirming its strong association with pre diabetes. Age group (OR = 2.27, p < 0.001), also showed a substantial effect, Sex (OR = 1.95, p < 0.001), physical activity (OR = 1.69, p < 0.001), Overweight (OR = 1.39, p < 0.0034) and Fasting blood sugar (OR = 1.33, p < 0.0034) were also significant predictors. However, alcohol consumption and underweight were not statistically significant. Metabolic indicators along with physical inactivity are critical factors influencing prediabetes in young adults. Early screening and targeted lifestyle interventions are essential in preventing diabetes progression, and reducing the risk of future health burdens.